KECEPATAN LELEH, WARNA DAN TEKSTUR SECARA SENSORIS ES KRIM DENGAN PENAMBAHAN SARI BUAH BIT MERAH (BETA VULGARIS L.) - Setiawan, Ayu Rosa; Setyawardani, Triana; Widyaka, Kusuma (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The aim of this study was to examine the effect of adding red beetroot juice (Beta vulgaris L.) with different percentages on the melting speed, color and texture of ice cream sensoryly. Materials and methods. Treatment using 100% cow's milk added 0% red beet juice; 7%; 14%; 21%; 28%; Each treatment was repeated 4 times. The study used a completely randomized design (CRD) for the variable melting rate, and a randomized block design (RBD) for sensory tests (color and texture) with 15 semi-trained panelists. The results showed that the treatment had a very significant effect (P<0.01) on the melting speed, color, and texture of ice cream. Results. The results showed that the melting speed of ice cream ranged from 15.22-18.39 minutes/gram following the equation Y= 0.1152x + 15.109 with a coefficient of determination (R2) = 84.65%; the color ranges from 1.80 to 4.13 (dislike-very much) following the equation Y= 0.1152x + 15.109 with a coefficient of determination (R2) = 19.54%; and texture ranged from 2.00–4.00 (dislike-very much) following the equation Y= 0.061x + 2.146 with a coefficient of determination (R2) = 18.20%. Conclusion. Addition of red beet juice as much as 28% the longest melting speed of ice cream compared to other treatments. The addition of 14% red beet juice with a perfect red ice cream color was very liked by the panelists. The addition of 28% red beet juice with an ice cream texture was highly favored by the panelists.